Bullying prevention literacy through educational quartet card games for junior high school students in Makassar City - Suriah Suriah; Muhammad Syafar; Rizky Chaeraty Syam; Wisnah Lenna; Nabilah Gandi; Suci Nurul Karunia Rahim; Abnia Misliah Zahrah; Muhammad Farhan Khaliq; Muhammad Rachmat (Community Empowerment, 2024)
Bullying is an intentional act of violence aimed at disturbing others, both physically and psychologically, and has long been a part of school dynamics. Throughout 2021, the Indonesian Child Protection Commission (KPAI) recorded 17 cases involving students and educators, with a bullying incident in 2022 resulting in the death of a junior high school student victimized by nine friends. This community service activity aims to enhance students' understanding of bullying behavior, particularly those in island areas. Efforts include increasing their literacy about positive behavior to prevent various forms of bullying, such as physical, verbal, social, or cyberbullying. The method involves a combination of lectures and educational games, using Muslim children's quartet cards. The results indicate an increase in participants' knowledge scores from 66.67% (pre-test) to 83.33% (post-test) after bullying prevention education. The initiative aims to encourage reporting of bullying incidents in schools involving both teaching staff and students as a preventive measure.